FINANCIAL PERFORMANCE ANALYSIS AT PT. MAHA PROPERTY INDONESIA, Tbk - Andi Sartika Juniarmita, Andi Sartika Juniarmita; Amalia Febrianti Imran, Amalia Febrianti Imran; Auliyah Nurwafiyyah, Auliyah Nurwafiyyah (Jurnal Manajemen Dan Bisnis, 2023)
Financial Performance Analysis at PT. Maha Properti Indonesia, Tbk. The purpose of this study was to determine the financial performance of PT. Maha Properti Indonesia, Tbk. The type of data used in this research is quantitative data. The source of data is secondary data. The analytical method used in this research is financial ratios. The results showed the financial performance of PT. Maha Properti Indonesia, Tbk fluctuated. Based on the Liquidity Ratio, the current ratio decreased by 0.19%, the quick ratio decreased by 79.50% and the cash ratio increased by 0.18%. Based on the Solvency Ratio, debt to assets increased by 0.23%, debt to equity increased by 0.30% and long-term debt to equity decreased by 0.1%. Based on the Profitability Ratio, ROA decreased by (0.79%), ROE decreased by (103%). Based on the activity ratio, GPM decreased by 40.67%, NPM decreased by (20.86%), ARTO increased by 21.03 times, WCTO decreased by 0.84 times. FATO decreased by 14.83 times, TATO decreased by 0.037 times. The hypothesis in this study was rejected.